Pengaruh Penerbitan Opini Going Concern pada Pergantian Auditor dengan Ketepatwaktuan Pelaporan Keuangan dan Komite Audit sebagai Variabel Pemoderasi - Trisna Dewi, Sri Rahayu; Dwirandra, A.A.N.B.; Dwija Putri, I G.A. Made Asri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.02.TAHUN 2016, 2016)
The mandatory auditor switching require companies to switch auditors after audited for three consecutive years by the same auditor. But there is also non mandatory auditor switching which usually can result from the issuance of the auditor's going concern opinion. Effect of a going concern opinion is not linear at the auditor switching, but there are other variables that moderate, including, timeliness of financial reporting and the audit committee. The population used in this study are all companies listed on the Indonesia Stock Exchange in 2010-2012 with selection method sample using purposive sampling. Hypothesis testing is performed using binary logistic regression. The results showed the issuance of going concern opinion has a positive effect on the possibility of auditor switching. Timeliness of financial reporting and the audit committee did not moderate the effect of the issuance of a going concern opinion on the possibility of a auditor switching. The results also show the interaction of the issuance of going concern opinion, timeliness of financial reporting and audit committee has no effect on the possibility the company were switch auditors. Keywords : issuance of going concern opinion, timeliness of financial reporting, the audit committee, auditor turnover